Exploration of barriers to postnatal care service utilization in Debre Libanos District, Ethiopia: A descriptive qualitative study - Girma Tareke, Kasahun; Feyissa, Garumma Tolu; Kebede, Yohannes (Frontiers in Global Women's Health, 2022)
Background: In Ethiopia, postnatal care (PNC) service utilization was low despite many interventions were implemented. Previous studies showed community/caregiver related barriers to PNC service utilization, but limited evidence was available on the health facilities and health care providers related barriers. Therefore, the study was aimed at exploring both community and health care provider-related barriers to PNC service utilization. Methods: A descriptive qualitative study was conducted at Debre Libanos district, Ethiopia, from March 11 to April 7, 2019. A purposive sampling technique was used to recruit study participants among recently delivered women (< 2months), health care providers, and community members. A total of five in-depth interviews, twelve key informant interviews and four FGDs were conducted with a total of fifty-two participants. Data were audio-recorded, transcribed verbatim, and translated, and inductive thematic analysis was used to analyze the data using the atlas ti.7.1 software. Results: The findings were organized into two major themes: 1) Community/caregiver related barriers to PNC service utilization: lack of awareness about PNC, its importance, and schedules; lack of awareness about postnatal danger signs, sociocultural and religious beliefs, topographical and transportation problems, non-functionality of the health developmental armies (HDA); 2) health facility and health care provider-related barriers to PNC service utilization: poor supportive supervision and monitoring, lack of health extension workers ( HEW) commitment, lack of an organized system to notify delivery to HEW, shortage of HEWs, residence of the HEWs, closure of health posts (HP) on working hours, and non-functionality of HPs. Conclusions: The study findings underscore the need to develop different strategies and taking actions. Therefore, the health centers and district health office should have to assign the required number of HEWs at HPs, regularly supervise and monitor HEWs, and develop an organized system to facilitate early notification of delivery to HEWs. The HEWs should have to live near the HP, re-organize HDAs, create awareness on the maternal and newborn danger signs, and conduct social and behavioral change communications to increase the health-seeking behavior of community members for utilizing PNC services.